Quantitative ethnobotanical study of medicinal flora used by local inhabitants in selected Barangay of Malinao, Albay, Philippines - TERESA HAIDE BELGICA; Marlon Suba; Grecebio Jonathan Alejandro (Society for Indonesian Biodiversity, 2021)
Abstract. Belgica THR, Suba MD, Alejandro CJD. 2021. Quantitative ethnobotanical study of medicinal flora used by local inhabitants in selected Barangay of Malinao, Albay, Philippines. Biodiversitas 22: 2711-2721. study identified and documented herbal medicines used in traditional therapies of local inhabitants in Malinao Albay. Ethnobotanical documentation in this study was through field observation, unstructured interviews, group discussions, and guided field walks. Preference ranking, use-value, informant consensus factor, and fidelity level were quantified. Based on the survey, 74 medicinal plants from 38 families and 72 genera were identified by 350 local inhabitants with therapeutic purposes using quantitative ethnobotanical indices. The plant species belonging to Lamiaceae were best represented with eight species, followed by Compositae with six species and Euphorbiaceae, Malvaceae, and Moraceae with four species each. While the plant species, i.e., Senna alata (L.) Roxb and Pogostemon cablin (Blanco) Benth, were recorded with the highest Fidelity level (FL). In terms of Informant Consensus Factor (ICF), Justicia gendarussa Burm.f, Lagerstroemia speciosa (L.) Pers and Centella abbreviata (A. Rich.) Nannf were recorded with the highest values. Moreover, the plant with the highest Use Value (UV) was Moringa oleifera Lam, and the leaves were the most used part as a decoction to cure different illnesses. This study provides baseline data of plant diversity in Malinao Albay and their medicinal uses, which could be used as a basis for drug discovery to improve the utilization of herbal plants from global perspectives.